Influence of Transformer Design in AC/DC/AC Converter Output Circuits on Plasma Reactor Characteristics - Komarzyniec, Grzegorz; Boiko, Oleksandr; Danuta Stryczewska, Henryka (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Three-phase arc discharge plasma reactors are challenging to maintain stable plasma parameters. Plasma performance is significantly influenced by the design of the power system and its output characteristics. This paper examines the interaction of a plasma reactor with an AC/DC/AC converter equipped with different transformer solutions to adapt the output parameters to the requirements of the plasma reactor. The design of transformers has a significant impact on the parameters of the generated plasma and the reactor's interaction with the power grid. The performance characteristics obtained for these solutions indicate that the design of the transformers has a strong influence on the performance characteristics of the reactor.